A cross-sectional ecological study of the impact of sand mining on biodiversity in the Umdloti River, KwaZulu-Natal – A qualitative study. (Student's Journal of Health Research Africa, 2025)
BackgroundSand mining is an escalating threat to riverine ecosystems, especially in developing regions where construction demands are high. In KwaZulu-Natal, the Umdloti River has seen a surge in sand mining, raising concerns about its impact on biodiversity and habitat integrity. This study investigates the ecological effects of sand mining along the Umdloti River, focusing on macroinvertebrate diversity, vegetation cover, and habitat condition. MethodsA cross-sectional ecological assessment was conducted in April 2024 across three zones: an active sand mining site, an upstream control site, and a downstream recovery site. Macroinvertebrates were sampled using the South African Scoring System (SASS5), while aquatic and riparian vegetation was surveyed using species richness transects. Habitat condition was evaluated based on channel morphology, substrate type, bank stability, and turbidity. Comparative analysis employed descriptive statistics and ANOVA. ResultsMacroinvertebrate diversity and SASS5 scores were significantly lower in the mining zone, with sensitive taxa absent and pollution-tolerant species dominating. Vegetation cover was reduced, with indigenous species displaced by invasive colonizers. Habitat assessments indicated degraded conditions, including unstable banks, altered channel structure, and elevated turbidity. The control zone exhibited greater biodiversity and intact habitats, while the downstream zone showed signs of partial recovery but remained impacted. ConclusionSand mining along the Umdloti River has led to measurable biodiversity loss and ecological degradation, disrupting both aquatic and riparian systems. RecommendationsImmediate regulatory interventions are needed, including buffer zone enforcement, rehabilitation of mined areas, and stricter permitting controls. Long-term ecological monitoring should be implemented to assess recovery trends. Engaging local communities and stakeholders in sustainable alternatives to unregulated sand extraction is critical to safeguarding the river’s ecological integrity.
Keywords: Sand mining; Riverine biodiversity; Macroinvertebrates; Habitat degradation; Umdloti River; Riparian vegetation; Ecological assessment; SASS5; Sedimentation; Environmental regulation